Cartel Stability and Economic Integration - Philipp J. H. Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This paper investigates the effect of economic integration on the ability of firms to maintain a collusive understanding about staying out of each other?s markets. The paper distinguishes among different types of trade costs: ad valorem, unit, fixed. It is shown that for a sufficient reduction of ad valorem trade costs, a cartel supported by collusion on either quantities or prices will be weakened, thus integration is pro-competitive. If integration consists of a reductions in unit (fixed) trade costs a price setting cartel is strengthened (unaffected), while a quantity setting one is weakened.
Keywords: F15; F12; L12; L13; 330; Collusive behavior; trade liberalisation; specific tariffs; market access cost; Kartell; Wettbewerbsbeschränkung; Aussenhandelsliberalisierung; Wirtschaftsintegration; Zolltheorie; Kosten; Theorie